The influence of destination image and tourist satisfaction on positive word of mouth and revisit intention on the island of Bali - Wulansari, Indah; Andajani, Erna (Southeast Asian Journal of Service Management, 2024)
This research aims to determine the effect of Destination Image and Tourist Satisfaction on Positive Word of word-of-mouth recommendations and Revisit Intention on the island of Bali. The island of Bali is an island that has a world-class tourist attraction. One of the unique Bali tours is the culture of the island of Bali itself. The variables used in this study include Destination Image, Tourist Satisfaction, Positive Word of word-of-mouth recommendation, and Revisit Intention. This study uses quantitative research using primary data through questionnaires to respondents who have visited the island of Bali with a total of 170 respondents. Data processing in this study uses SEM (Structural Equation Modeling) with SPSS and AMOS software. The results of this study indicate a significant effect on Destination Image and Tourist Satisfaction on Positive Word of word-of-mouth recommendation and Revisit Intention.